Presentation reviewing system - Albazzai, Norah (2015)
Group projects is one of the main activities in many organizations. Presentations’ creation by groups is a common task to deliver different content. In order to achieve presentation satisfaction by group members, there is a need for an evaluation session that requires collecting notes and comments. Many systems attempt to offer technical solutions that provide one or more tools to control specific situation within reviewing meetings. Therefore, the new system was developed as a single solution to control many issues that might occurs in such meeting. The system is a web-based system that can be used during groups meetings for reviewing a multiple slides presentation draft. The system enables group members from writing notes privately using their own devices at the same time without disturbing the presenter. At the end of the presentation, all the notes and feedback can be reviewed in the presenter screen in an organized way. In this dissertation, many methods and techniques were used to develop the system. Interviews is one of the methods that were conducted for two purposes: requirements collection and system testing. Designing the system structure was visually represented using Unified Modelling Language (UML) and Entity Relationship Diagram (ERD). For implementing and testing the system, node.js was the main technology used. Combining all these tools enabled building of the presentations’ reviewing system. Eventually, the dissertation concludes that the new system offers suitable tool for technical management of reviewing sessions.